A systemic approach for disruption risk assessment in oil and gas supply chains. (25th March 2019) - Alfaqiri, Abdulrahman; Hossain, Niamat Ullah Ibne; Jaradat, Raed; Abutabenjeh, Sawsan; Keating, Charles B.; Khasawneh, Mahmoud T.; Pinto, C. Ariel
Twenty-first century systems are characterised by rapid changes and constantly evolving dynamics. Therefore, supply chains have become more globalised and complex than ever before. Global supply chains are often accompanied by serious threats and significant additional risks to industries that rely heavily on them. The oil and gas industry encounter significant supply chain risks throughout all stages. The objective of this paper is to provide a holistic complex system governance (CSG) perspective to investigate disruption risks in oil and gas supply chains. As a case study, the piracy problem in Africa is used to demonstrate the efficacy and extensibility of the CSG perspective to a wider array of potential supply chain disruptions. Unlike ready-made solutions or 'off-the-shelf' strategies that may actually undermine the establishment of a resilient global oil and gas supply chain, this paper examines associated risks as a complex system, or a system of systems problem.